Influence of Risk Management on Project Implementation, a Case Study of Indoor Residual Spraying Project in Rwanda - Karera Godfrey, Kasiita (International Journal of Scientific Research and Management (IJSRM), 2022)
The study entitled “Influence of Risk Management on Project Implementation, a case of Indoor Residual Spraying (IRS) Project in Rwanda”. The purpose of the study was to investigate the influence of project risk management on project implementation in Rwanda with reference to Indoor Residual Spraying (IRS) Project.  The study was guided by  four specific objectives: to examine the influence of project risk identification on implementation of Indoor Residual Spraying (IRS) Project, to assess the influence of Project Risk Analysis on the implementation of Indoor Residual Spraying (IRS) Project, to find out the influence of project risk response planning on the implementation of Indoor Residual Spraying (IRS) Project and to ascertain the influence of Project risk monitoring and control on the implementation of  Indoor Residual Spraying (IRS) Project. The research designs that were used in this study are descriptive research design and analytical research design. The study used 83 employees of Indoor Residual Spraying (IRS) Project as sample size. The study used stratified sampling techniques to select   whole population to participate in this study. The study used questionnaires, interview guide and documentary review as method of data collection and finally the study used descriptive statistics and inferential statistics such as correlation analysis and multiple linear regression analysis as method of data analysis. For the first objective, the findings revealed that there existed a significant moderate positive correlation (R = 0.552**, p-value=0.002